2002
DOI: 10.1001/archpsyc.59.10.905
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Lifetime Panic Spectrum Symptoms in the Treatment of Patients With Bipolar I Disorder

Abstract: The presence of lifetime panic spectrum symptoms in this sample of patients with BPI disorder was associated with greater levels of depression, more suicidal ideation, and a marked (6-month) delay in time to remission with acute treatment. Alternate treatment strategies are needed for patients with BPI disorder who endorse lifetime panic spectrum features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
2
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(119 citation statements)
references
References 35 publications
9
106
2
2
Order By: Relevance
“…Elevated rates of additional psychiatric comorbidity in patients with 2 versus 1 presenting disorder have been documented in a number of psychiatric populations (e.g., 20,21). Nevertheless, given that both obesity and anxiety comorbidity have been shown to correlate with indicators of poor prognosis in bipolar patients (e.g., delayed response to treatment, shorter time to recurrence) (22,23), future studies are needed to determine the impact of aberrant eating on the clinical course of bipolar disorder and its treatment. In addition, research to tease apart the temporal and pathophysiological relationships among eating disorder symptoms, obesity, mood disorder history, and other psychiatric co-morbidity seems warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated rates of additional psychiatric comorbidity in patients with 2 versus 1 presenting disorder have been documented in a number of psychiatric populations (e.g., 20,21). Nevertheless, given that both obesity and anxiety comorbidity have been shown to correlate with indicators of poor prognosis in bipolar patients (e.g., delayed response to treatment, shorter time to recurrence) (22,23), future studies are needed to determine the impact of aberrant eating on the clinical course of bipolar disorder and its treatment. In addition, research to tease apart the temporal and pathophysiological relationships among eating disorder symptoms, obesity, mood disorder history, and other psychiatric co-morbidity seems warranted.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Reports of the prevalence of suicidal ideation vary from 14% to 59% in bipolar samples [20][21][22][23][24][25] and only a few cross-sectional studies have examined variables that influence suicidal ideation in BD and its relationship with suicide attempts. Some risk factors associated with the presence of suicidal ideation are positive family history for affective disorder, severe depression, 12 psychotic symptoms, 26 past suicide attempt, 23,26 comorbidity with alcohol abuse or dependence, 23 panic spectrum symptoms, 27 and earlier age of onset. 28 Valtonen et al, in a cross-sectional study with a sample of 191 patients with bipolar disorder, showed that 61% (n = 116) reported suicidal ideation during the index-episode and 20% (n = 39) had attempted suicide in the same episode.…”
Section: Stress-diathesis Modelmentioning
confidence: 99%
“…26,27 Comorbid psychiatric disorders (that is, dysthymia or obsessive-compulsive disorder (OCD)) could also reduce the overall response to treatment, or in some case could modify its timing. [28][29][30] Moreover, from a genetic perspective, the comorbidity with anxiety disorders, in particular the presence of panic-agoraphobic spectrum symptoms has been reported to be related with a different genetic background. 31 However, comorbidity is present to a large extent in depression, 32 and the exclusion of all comorbid patients will eventually again reduce representativeness.…”
Section: Clinical Features Of Depressionmentioning
confidence: 99%